2015
DOI: 10.1542/peds.2015-0326
|View full text |Cite
|
Sign up to set email alerts
|

Parent/Adolescent Weight Status Concordance and Parent Feeding Practices

Abstract: Background Prior studies have examined the independent influence of mothers’ weight status or childs’ weight status on parents’ use of specific feeding practices (i.e., restriction, pressure-to-eat). However, studies have not examined the mutual influence of parents' and adolescents' weight status on parents' feeding practices. This study examines the relationship between parent/adolescent weight status concordance and discordance and parent feeding practices. Methods Data from two linked population-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 58 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…No significant difference was found on PFQ pushing the child to eat more [67], CFQ pressure to eat [68,70,72,74,75,80], PFSQ prompting/encouragement to eat [77] CFPQ pressure [73], and laboratory observational prompting a child to eat [81]. One study however, reported that parents with healthy-weight used significantly higher levels of CFQ pressure to eat when compared to parents with overweight and obesity, suggesting that parents with overweight/obesity use pressure to eat less [79]. Francis and colleagues [68] reported that pressure to eat by mothers with overweight/obesity was significantly predicted by daughters' adiposity, and mothers' concern for daughters' weight.…”
Section: Pressure To Eatmentioning
confidence: 92%
See 3 more Smart Citations
“…No significant difference was found on PFQ pushing the child to eat more [67], CFQ pressure to eat [68,70,72,74,75,80], PFSQ prompting/encouragement to eat [77] CFPQ pressure [73], and laboratory observational prompting a child to eat [81]. One study however, reported that parents with healthy-weight used significantly higher levels of CFQ pressure to eat when compared to parents with overweight and obesity, suggesting that parents with overweight/obesity use pressure to eat less [79]. Francis and colleagues [68] reported that pressure to eat by mothers with overweight/obesity was significantly predicted by daughters' adiposity, and mothers' concern for daughters' weight.…”
Section: Pressure To Eatmentioning
confidence: 92%
“…The oldest studies included in the review were published in 2001 [67,68] and the most recent studies were published in 2018 [65,69] (Table 1: Study Results Table can be found in supplementary materials, S1). Of the twenty relevant studies, sixteen were cross-sectional [67,68,[70][71][72][73][74][75][76][77][78][79], three were observational [80][81][82], and one longitudinal [83]. Research was conducted in the USA (n = 9), the UK (n = 2), Germany (n = 2), Turkey (n = 1), Australia (n = 1), Australia and New Zealand (n = 1), Brazil (n = 1), The Netherlands (n = 1), Poland (n=1) and China (n = 1).…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, adolescents were more physically active if their parents engaged in PA more often, or if they perceived higher parental support for PA (Graham et al, ). Relationships are also important: having strict parents is associated with healthier behaviors (Alia, Wilson, George, Schneider, & Kitzman‐Ulrich, ; Berge, Meyer, Loth, MacLehose, & Neumark‐Sztainer, ). The effect of family structure (e.g., who lives in the home) was inconclusive in some studies (Hohepa, Scragg, Schofield, Kolt, & Schaaf, ), whereas others found that adolescents with two parents had healthier dietary behaviors (Levin & Kirby, ; Pearson, Atkin, Biddle, Gorely, & Edwardson, ).…”
Section: Introductionmentioning
confidence: 99%